POPULATION DYNAMICS AND FISHERY OF SWIMMING CRAB, PORTUNUS TRITUBERCULATUS IN THE ZHEJIANG FISHING AREA, EAST CHINA SEA - S. K. Panhwar; Z. Y. Dong; L. Zhenghua; S. Rashid; H. Zhouting; G. Ai; W. Ping (Journal of Animal and Plant Sciences, 2018)
This study demonstrates dynamics of growth, mortality, exploitation, maximum sustainable yield of swimming crab, Portunus trituberculatus in Zhejiang, East China Sea. Using two types of fishery data, one type is the carapace length, width ( in mm) and weight ( in g) of 3,176 individuals of swimming crab collected by the scientific voyages conducted in 2005-2016. The other is the time series of catch and effort data from 2005 to 2016. The estimated population parameter from twelve-years pooled data sets were used to estimateyear-on-year variation in asymptotic length (L ) , growth (K), total mortality (Z), fishing mortality ( F), natural mortality (M), and biological reference points of F and F . Time limit opt series catch and catch per unit effort data sets ( 2006-2015) obtained from two fishing methods gill net and crab pot net fishery were used to estimate maximum sustainable yield (MSY) with two surplus production models of Fox and 2 2 Schaefer. The MSY estimates from Fox model 42.79 tonnes, R =0.85 and Schafer model, 34.12 tonnes, R =0.79. Based on the outputs from two types of fishery data it is delineated that biological reference points of fishing limitation ( F ), limit optimum fishing level ( F ) and maximum sustainable yield (MSY) from two production models for swimming crab opt have been overharvest. To overcome current situation recently swimming crab seed was released in Zhoushan coastal area that can augment recruitment and rebuild stocks. The cohesive data sets presented in this communication would increase understanding about crab population traits and can help in implementation of reasonable measures. difficult to study or unavailable, in these cases length data
Keywords: Portunus trituberculatus; population dynamics; fishery; biological reference points; Zhejiang waters.